Sistem Pemilah Tingkat Kematangan Pinang Menggunakan Sensor TCS3200 dan Monitoring Menggunakan Telegram - Yasa Khalqiah; Irma Nirmala; rahmi, rahmi (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Betel nut is one of West Kalimantan's leading export commodities. In its utilization, raw betel nut can be processed into juice and medicine, ripe betel nut can be used as a textile dye and cosmetic ingredients, and old betel nut can be used as a mixture in betel consumption. The sorting process is done with the TCS3200 sensor, which is monitored in real-time using a telegram bot. The system is controlled by Arduino and uses hardware such as servo motor type MG90S, NodeMCU ESP32, and conveyors. Loadcell sensor measures the weight of the betel nut, while the HC-SR04 Ultrasonic sensor determines the height of the container. The results using 90 samples of betel nut show the accuracy in sorting using the TCS3200 sensor is 88.89%, while the average relative error of measuring betel nut weight is 8.04%.